vm PERSEPSI MASYARAKAT TERHADAP STUNTING PADA BALITA (STUDI KASUS: NAGARI LUMPO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN: PERSEPSI MASYARAKAT TERHADAP STUNTING PADA BALITA (STUDI KASUS: NAGARI LUMPO KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Viona, meri; Karia, Waza; Rahayu, Sri (Publiciana, 2024)
This research was motivated by the extent of the community’s perception of stunting among This research was motivated by the extent of the community's perception of stunting among toddlers in Nagari Lumpo, IV Jurai District, Pesisir Selatan Regency. The aim of this research is to describe the public's perception of stunting in toddlers (Case Study: Nagari Lumpo, IV Jurai District, Pesisir Selatan Regency). This research uses functional structural theory according to Talcott Parsons. This discussion of functionalism will begin with the four AGIL schemes. The results of research on Community Perceptions of Stunting in Toddlers in Nagari Lumpo, IV Jurai District, Pesisir Selatan Regency, there are two community groups, namely; First, the perception of communities related to stunted toddlers, which includes; Stunting is a disease, stunting makes families feel ashamed and stunting makes children's families feel excluded. Second, the general public's perception (not having a family relationship with a stunted toddler) includes; Stunting is malnourished children, stunting is parents who cannot take care of their children and stunting comes from families that don't live a clean life. Keywords: Perception, Stunting, Society, Toddlers